Nonlinear finite element analysis of prestressed concrete box section beams - Al-Shaarbaf, Ihsan A. S.; Abbas, Hiba Emad (Nahrain University College of Engineering Journal, 2017)
This study presents a three-dimensional nonlinear finite element model suitable for the analysis of prestressed concrete box beams up to failure. Concrete was modeled using three-dimensional 20- node isoparametric quadratic brick elements, while the prestressing and reinforcing bars were modeled as one dimensional axial members embedded within the concrete elements. The behavior of concrete in compression is simulated using an elasto-plastic work hardening model followed by a perfectly plastic response, which is terminated at the onset of crushing. In tension, a smeared crack model with orthogonal cracks has been used with the inclusion of a model for the retained post-cracking tensile stresses and a model that reduces the shear modulus of rigidity after cracking. The nonlinear equations of equilibrium have been solved using an incremental-iterative technique based on the modified Newton-Raphson methods. The numerical integrations have been carried out using the 27-Gaussian- quadrature integration rule. Different types of prestressed concrete beams have been analyzed, and the finite element solutions are compared with the available experimental data. The finite element results obtained were the load-deflection response. Several parametric studies have been carried out to investigate the effects of some important finiteelement and material parameters on the behavior of prestressed concrete box section beams. In general, good agreement between the finite element solutions and the available experimental results has been obtained. A study was made to compare the finite element ultimate moment of prestressed concrete box beams obtained for different values of compressive strength of concrete and area of prestressing steel with the provisions of the ACI-Code (318M-05). It was found that the predicted values of the ultimate moments obtained using the finite element analysis are in good agreement with the corresponding values obtained using the provisions of the ACI-Code (318M-05).